Sunday

April 20, 2014

April 20, 2014

Posted by **flame** on Saturday, October 2, 2010 at 8:43pm.

for example,

case A: 2y=3x+c

is y=(3x/2)+c

case B: -3y=x+c

is y= (-x/3)+c

case C: -y=x+c

is y=-x-c

- calculus -
**bobpursley**, Saturday, October 2, 2010 at 8:46pmI dont know what you mean " need to time the constant c by a number"

It doesn't matter, since it is still a constant, if you take the derivative, the constant goes to zero anyway.

**Related Questions**

Math- Adv. Alg. w/ Trig. - I need help simplifying this expression: (3x^3y^5 + ...

math correction - solve for x: 3x - 2y = 6 i need help in solving this: the ...

dwrls,math - PLEASE LOOK IN THE BOTTOM OF THIS MESSAGE...... solve for x: 3x - ...

algebra 1 - Why Does A Poor Man Drink Coffee? use the and y-intercept to graph ...

derivative - I am finding the second derivative of (x^2)(y^3) = 1 2x(y^3) + (x^2...

Algebra - How do I solve for elimination method on this problem: 0.3x - 0.2y=4 ...

algebra - needing help with is problem solve for x: 3x-2y=-6 here is my solution...

Algebra - What is the standard form of the equation of the line passing through ...

maths - solve the following simultaneous equation: 5x+2y=29 x-y=-4 2x-y=-1 3x-y=...

algebra - how do I do this Solve for x. 3x – 2y = 6 Add 2y to both sides and ...